(3Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s ((3Ydj Hf YHOGddg Hf Ydj GdSeQehj GdTGaYj GdbQTj s)
(3ChdgG (B:s
(3bGd Mfjf Hf ESMGb Efg dMbfi ef GdcGaQjf HfYeJi GdLGMOjf dMbi s
(3BNQgG (B:s
(3hdg ef GdcJH JYGdjb , GdcjejGA , cJGH ai Yde GdfLhe , eNJGQGJ aj GdWH s
(3GdLRA GdKGfj ef fSNI SGOSIs
(3YdjgG oeWGdYI dLdGd GdOjf Hf GdTQajs
(3hMSf Hf eMeO GdYWGQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs